Priklausymo atributiniai junginiai - Bučienė, Laimutė (Kalbotyra, 2004)
Possessive phrases indicate the belonging of a thing or its other relations. In the case of inalienable possession a possessed thing cannot be separated from the possessor without breaking its integrity. Such phrases denote the relations of the whole complex to its part (e. g. merginos pirštai, namo langai, žmogaus siela, pyrago skonis, savimeilės išraiška). The possessed things in alienable possession are not perceived as necessary or possible to the possessor in general. Alienable possession expresses kinship (dukros sūnus), position (vedėjo sekretorė), ownership (mano mašina), authorship (Maironio eilėraštis) relations.